The Impact of Macroeconomic Determinants on the Development of the Digital Economy: A Dynamic Approach Using Panel GMM for Selected Countries (مجلة دراسات إقلیمیة, 2026)
This study examines the impact of key macroeconomic determinants on the development of the digital economy in a panel of emerging and developing countries—India, Turkey, Jordan, Kuwait, Egypt, Tunisia, Qatar, Iraq, Thailand, South Africa, Morocco, Malaysia, and Indonesia—over the period 2010–2025. The analysis employs a dynamic panel approach using the Generalized Method of Moments (GMM) to address endogeneity and ensure robust results. The findings reveal that broad money and domestic credit to the private sector play a significant role in fostering digital expansion by enhancing liquidity and widening access to finance. Gross capital formation emerges as a crucial driver of digital infrastructure and technological capacity, while trade openness facilitates technology transfer and knowledge spillovers. The effect of the current account balance is found to be heterogeneous, reflecting structural differences among the sampled countries. The study concludes that strengthening macroeconomic stability, deepening financial intermediation, and promoting investment in digital infrastructure are key strategies to accelerate digital transformation and achieve sustainable economic growth.